Literasi Gender Posthuman di Pendidikan Tinggi Indonesia: Platform, Kebijakan, Infrastruktur, dan Rangkaian Keadilan Digital - Anjarsari, Fitrilya (SERUNAI, 2025)
This article examines how gender is co-produced by humans, technologies, and institutions in Indonesian higher education, reframing “gender literacy” as a posthuman assemblage rather than an individual competence. Existing studies on gender education largely focus on attitudes, curriculum content, or gender mainstreaming outcomes, leaving underexplored how learning management systems, surveillance, uniforms, and administrative forms silently encode and enforce gender norms. Addressing this gap, the study proposes a framework of posthuman gender literacies that maps intra-actions among students, devices, platforms, and regulatory texts. Motivated by tensions between state commitments to gender equality, ed-tech expansion, and persistent exclusion of non-normative bodies, the research seeks to clarify how seemingly neutral educational technologies reproduce or unsettle gender binaries. Methodologically, the study employs qualitative multi-sited research in two Indonesian universities, combining policy analysis, platform/interface walkthroughs, and critical multimodal discourse analysis of online classrooms, forms, and assessment dashboards. Preliminary findings indicate that platform defaults, data categories, and interfaces strongly steer students toward binary, heteronormative identities while also opening small spaces for tactical subversion. These insights inform national gender mainstreaming agendas and campus-level governance. The article concludes by outlining policy implications for gender-responsive ed-tech design, institutional data categories, and lecturer training oriented to posthuman gender justice.